2000
DOI: 10.1054/bjoc.1999.0967
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous apoptosis in ovarian carcinomas: a positive association with p53 gene mutation is dependent on growth fraction

Abstract: Changes in cell survival contribute to tumour development, influence tumour biology and its response to chemotherapy. p53 gene alterations should negatively affect apoptosis by impaired p53-dependent apoptotic response. We looked for associations between spontaneous apoptosis, p53 gene mutation, p53 protein accumulation, growth fraction, bcl-2 expression and histological parameters in 64 ovarian, four tubal and three peritoneal carcinomas. Apoptotic cells were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…(Kupryjanczyk et al 2000); # -TP53 accumulation (+), lack of TP53 accumulation (-) has been determined previously (Kupryjanczyk et al 2000(Kupryjanczyk et al , 2003; S-serous, M-mucinous, E-endometrioid, C-clear cell, O-other (transitional cell carcinoma, carcinosarcoma, undifferentiated, unclassified).…”
Section: Tp53 Gene Mutations In the Polish Populationmentioning
confidence: 88%
See 2 more Smart Citations
“…(Kupryjanczyk et al 2000); # -TP53 accumulation (+), lack of TP53 accumulation (-) has been determined previously (Kupryjanczyk et al 2000(Kupryjanczyk et al , 2003; S-serous, M-mucinous, E-endometrioid, C-clear cell, O-other (transitional cell carcinoma, carcinosarcoma, undifferentiated, unclassified).…”
Section: Tp53 Gene Mutations In the Polish Populationmentioning
confidence: 88%
“…The total number of alterations that resulted in the formation of a truncated protein (also verified immunohistochemically by the lack of TP53 protein accumulation; Kupryjanczyk et al 2000Kupryjanczyk et al , 2003 was 34 out of 103 (33% of all mutations). Two in frame errors (exon 6, tumour 165; exon 5, tumour 172), two splice-site mutations (exon 5, tumour 280; exon 10, tumour 311) and one nonsense mutation (exon 7, tumour 351) resulted in TP53 protein accumulation (Table 1).…”
Section: Tp53 Gene Mutations In the Polish Populationmentioning
confidence: 92%
See 1 more Smart Citation
“…K 5204, Dako, Glostrup, Denmark) served as controls for the procedure, as well as for the specificity of the CBE356 antibody. As a positive control for TP53, we used a tumour with a defined TP53 gene missense mutation (Kupryjanczyk et al, 2000). Normal mouse IgGs of the same subclasses and concentrations as the primary antibodies served as negative controls, too.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…The prognostic value of p53 protein accumulation has been a matter of controversy. It seems that p53 protein accumulation is a more adequate manifestation of impaired p53 protein function than a marker of gene alterations that also may include nonsense errors without protein accumulation (4) . Schildkraut et al (12) have demonstrated in a study on 197 patients with ovarian cancer (72 patients with early and 125 patients with advanced FIGO stages), that p53 overexpression, FIGO stage, and age were independent predictors of survival if the patients at time of diagnosis were younger than 55 years.…”
mentioning
confidence: 99%